2022
DOI: 10.1155/2022/6073878
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Weaning among Mothers in Najran Region, Saudi Arabia, 2021

Abstract: Background. Weaning is a complex process of a gradual introduction of complementary foods to the infant’s diet. It is recommended that solid food is introduced between 6 and 12 months of age. Weaning is difficult and potentially dangerous time for infants’ growth and mother’s education is an established determinant of its success. Little is known about weaning attitudes or practice among mothers in Najran Region of Saudi Arabia. Method. The study is a cross-sectional questionnaire-based observational investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is also reported that a high level of weaning is associated with working women or working mothers. 42 Overall, the frequency of exclusive breastfeeding children was 269 cases (62.27) compared to 163 cases (37.73), which may be because of the common belief among the Chinese that breastfeeding reduces the burden of diarrhea and gastrointestinal infections. Studies have reported that breast milk contains secretory antibodies, IgA, and other immune cells that protect the intestinal epithelium from microbial pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…It is also reported that a high level of weaning is associated with working women or working mothers. 42 Overall, the frequency of exclusive breastfeeding children was 269 cases (62.27) compared to 163 cases (37.73), which may be because of the common belief among the Chinese that breastfeeding reduces the burden of diarrhea and gastrointestinal infections. Studies have reported that breast milk contains secretory antibodies, IgA, and other immune cells that protect the intestinal epithelium from microbial pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…Despite adequate educational qualifications, the infants were underfed. This was attributed to the fact that women preferred to follow local customs instead of seeking doctors' advice [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, its monotonous consumption has been associated with protein-energy (PEM) malnutrition in SSA. 3 In PEM, consumption of both energy and protein is insufficient leading to a form of hidden hunger and stunted growth in other cases kwashiorkor or marasmus. 4…”
Section: Introductionmentioning
confidence: 99%
“…Hence, its monotonous consumption has been associated with proteinenergy (PEM) malnutrition in SSA. 3 In PEM, consumption of both energy and protein is insufficient leading to a form of hidden hunger and stunted growth in other cases kwashiorkor or marasmus. 4 The supply of animal protein is insufficient to meet the protein needs in resource-limited communities, stimulating the research to efficiently combat PEM via cost-effective strategies.…”
Section: Introductionmentioning
confidence: 99%